Prevalensi Lepra Tahun 2019 – 2024 di Rumah Sakit - Lukman, Moudyana; Vitayani, Sri; Frisa, Selis (Jurnal Ilmiah Global Education, 2025)
Leprosy or Morbus Hansen is a chronic infectious disease with prominent involvement of the skin and nerves caused by the bacillus Mycobacterium leprae. Leprosy is divided into two main forms depending on the degree and type of immunity. Lepromatous lessing with a dominant Th2 response and tuberculoid with a dominant Th1 response. Early diagnosis and rapid treatment of all new cases of leprosy treated with multidrug (MDT) is a recommendation from the World Health Organization (WHO) is still a key strategy in controlling leprosy and further preventing nerve damage and disability. Objective: This report aims to know the prevalence of leprosy in 2019 - 2024 in Hospitals. Method: The method used is a literature review with a Narrative Review design. Results: The results obtained in this literature are 15 articles obtained with arrangement from 2020 - 2025 and an in-depth analysis of the strengths and weakness of each article has been carried out regarding the prevalence of leprosy in 2019 - 2024 in Hospitals, 15 articles mention the prevalence of leprosy in 2019 - 2024 in Hospitals. The most dominant characteristics of Hansen's disease in this literature review are age and type of Hansen's disease, followed by gender. Although there are several other characteristics such as occupation.